2002
DOI: 10.1073/pnas.152162299
|View full text |Cite
|
Sign up to set email alerts
|

The molecular structure of spider dragline silk: Folding and orientation of the protein backbone

Abstract: The design principles of spider dragline silk, nature's highperformance fiber, are still largely unknown, in particular for the noncrystalline glycine-rich domains, which form the bulk of the material. Here we apply two-dimensional solid-state NMR to determine the distribution of the backbone torsion angles ( , ) as well as the orientation of the polypeptide backbone toward the fiber at both the glycine and alanine residues. Instead of an ''amorphous matrix,'' suggested earlier for the glycine-rich domains, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
607
1
8

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(651 citation statements)
references
References 47 publications
32
607
1
8
Order By: Relevance
“…4b,d]). The initial regime is characterized by a relatively high tangent modulus (1.07 GPa) owing to the homogeneous stretching of semiamorphous regions that are rich in hydrogen bonding in the form of 3 1 -helices and beta-turns [1,6,22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b,d]). The initial regime is characterized by a relatively high tangent modulus (1.07 GPa) owing to the homogeneous stretching of semiamorphous regions that are rich in hydrogen bonding in the form of 3 1 -helices and beta-turns [1,6,22].…”
Section: Resultsmentioning
confidence: 99%
“…1a) [6][7][8]. Thereby, the anti-parallel beta-sheet nanocrystals [9][10][11][12] play a key role in defining the mechanical properties as they provide stiff orderly cross-linking domains embedded in a semiamorphous matrix that consists of less orderly beta-structures, 3 1 helices and beta-turns [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…2c, d), showing that the computational predictions yield excellent results when compared with empirical analyses. 26,27 Further details can be found in the original paper. 20 Further analysis of the resulting structures showed that the poly-alanine region and adjacent poly-glycine-alanine segments formed a stiff orderly cross-linking Fig.…”
Section: Molecular Structure and Mechanics Of Silkmentioning
confidence: 99%
“…The resulting configurations were validated against experimental data of structure and composition. 26 The resultant structures then allow for mechanical characterization on multiple scales as described in the subsequent figures. (b) Detailed view of the hydrogen bonding structure within different domains is identified with the model.…”
Section: Molecular Structure and Mechanics Of Silkmentioning
confidence: 99%
See 1 more Smart Citation